Analisis Isi Kuantitatif Konten Tiktok @vmuliana Selama Periode Satu Tahun (24 Februari 2021 – 24 Februari 2022) - Utami Sawitri, Dewa Ayu Agung; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2024)
The high use of TikTok in Indonesia has led to creative content shared by TikTok creators according to the interests and needs of TikTok users, one of which is work world content. The TikTok account @vmuliana is one of the accounts that is in demand and presents content about the work world.  TikTok @vmuliana has made an achievement as Best of Learning and Education TikTok Awards 2021. Therefore, this study aims to determine the types of content on the @vmuliana TikTok account and the frequency of occurrence of each category in the content uploaded by the @vmuliana TikTok account during one-year period ( 24 February 2021 – 24 February 2022) using new media theory. This research uses content analysis method and quantitative approach with qualitative data as supporting data. There are four categories of content types in this research including informational, relational, remuneration, and entertainment. The total uploads used as samples determined from the entire TikTok @vmuliana content population are 301 contents from 24 February 2021 – 24 February 2022. The results of the research findings show that the dominating content type category on TikTok @vmuliana is the informational category with 191 contents with a percentage of 63.45%, sequentially followed by relational content with 82 contents with a percentage of 27.24%, remuneration content with 15 contents with a percentage of 4.98% and entertainment content with 13 contents with a percentage of 4.31%.